Investigation on fouling of membranes for wastewater treatment and reuse - Aryal, Ashok (Curtin University, 2013)
Biological activated carbon (BAC) increases the molecular size of dissolved organic matter (DOM) in secondary wastewater treatment, thereby reducing membrane fouling. BAC is particularly effective in reduction of membrane fouling when used in conjunction with physicochemical treatment, and furthermore, the order of individual processes has been shown to be important. The increase in molecular size caused by BAC prevents clogging of membrane pores but also results in generally improved treatment performance for the physicochemical processes.